Nutzen und Nachhaltigkeit von Netzwerken zur betrieblichen Gesundheitsförderung in kleinen und mittleren Unternehmen – Am Beispiel der KMU-Netzwerke „Bewegte Unternehmen“ und „Vitale Unternehmen“ - Müller, Eva; Fischmann, Wolfgang; Kötter, Rudolf; Drexler, Hans; Kiesel, Johannes (Gesundheitswesen, 2018)
PURPOSE: The purpose of the study was to analyze if 2 regional networks of small and medium enterprises (SME) for workplace health promotion are sustainable, and to find out the motivation of the enterprises to join the network. It was also examined if there is a stable culture of cooperation 6 -10 years after the founding of the network. Additionally, the study checked the current work and suggestions for improvement to the network structure, so that in the future, promotion of workplace health can be further improved. METHOD: 2 regional networks, founded in 2005 and 2009, were studied. Standardized telephone interviews carried out between September 2013 and January 2014 enabled data collection for this cross-sectional study. 42 interviews with 6 open questions were organized with the managers of the companies or the person responsible for workplace health promotion. RESULTS: The results of the study show that 88.1% (n=37) of the network company members profited from the exchange of experiences. 50.0% (n=21) benefited from shared activities and 28.6% (n=12) from making new contacts. 9.5% (n=4) of the respondents expressed concerns about excessive bureaucracy resulting in too much effort for too little benefit and 7.1% (n=3) were also missing comprehensive structural measures. Suggestions for improvement were enhancement of practical work (26.2%, n=11) and the wish for stronger commitment (11.9%, n=5). 90.5% (n=38) considered their expectations as fulfilled and 66.7% (n=28) evaluated the current work as being quite positive. CONCLUSION: The networks have turned out to be sustainable, proven by the fact that the companies still are members of the networks for 6 and 10 years, respectively and are still satisfied with the network. The study shows that the majority of the members profits from the membership of these regional networks. Networks can help them to implement permanent workplace health promotion. To further improve the work of the network, a systematic and scientific workplace health promotion scheme is recommended.
EVALuna2:35294
Keywords: sustainability; workplace health promotion; benefit; SME; networks